Confirmation of human ovulation in assisted reproduction using an adhesive axillary thermometer (femSense®) - Weiss, Gregor; Strohmayer, Karl; Koele, Werner; Reinschissler, Nina; Schenk, Michael (Frontiers in Digital Health, 2022)
Objective: Timing for unprotected sexual intercourse is important in achieving pregnancy in natural cycles. Different methods of detecting the fertile window have been invented, among them luteinization hormone (LH) and biphasic body basal temperature (BBT) measurement or transvaginal ultrasonography in combination with serum LH and progesterone levels as gold standard in gynecology practice. In this study we evaluated a new temperature sensitive patch (femSense®) with continuous measurement of temperature to detect the fertile window. Methods: 96 patients received the femSense® system consisting of an adhesive axillary thermometer patch and a smartphone application. According to patients’ data the app calculated the patch application date and the most probable fertile window according to the respective temperature profile. Patients documented their daily urinary LH concentration, and a transvaginal ultrasound was performed on day 7, 10 and 12 of their cycle to investigate the growth of one dominant follicle. Ultrasound ovulation detection was performed on cycle day 14/15 combined with serum LH and progesterone measurement to confirm the results of the gynecologist. Detected ovulation dates of all methods (urinary LH test, femSense® system and ultrasound) were compared. Results: The femSense® system detected the ovulation in 60 cases (81.1%) compared to 48 ovulation detections (64.9%) with the LH test (p=0.02). Subgroup analysis revealed a positive trend for the femSense® system of specific ovulation detection within the fertile window of 24 hours after ovulation in 42 of 74 cases (56.8%) compared to 34 cases (45.9%) in the LH test group. Cycle length, therapy method or infertility reason of the patient did not influence accuracy of the ovulation detection methods. Conclusions: The femSense® system is a promising alternative to the traditional BBT method for ovulation detection.